Dependency of Specific Energy of Rock Cutting on Specific Drilling Energy (Rudarsko-geološko-naftni zbornik, 2018)
Specific energy is the measure which connects the operating parameters of the machine with the characteristics of the rock in which the machine works and is equal to the total work required to break a unit volume of the rock. It is assumed that in machines with the same or similar rock breaking mechanics used for different purposes (e.g. cutting and drilling of rocks), there is a significant dependence on their specific energy values. In the exploitation of dimension stone a chain saw and a rotary drill are often used, i.e. the machines for rock cutting or rock drilling whereas their mechanics of rock breaking is very similar. In order to determine dependence of the specific energy of rock cutting on the specific drilling energy, preliminary laboratory tests were carried out on a linear cutting machine and a laboratory drill with simulated cutting of rocks with a chain saw, and drilling by rotary drilling. The analysis of the measurement results has provided the guidelines for the continuation of laboratory testing, i.e. field testing.